2014
DOI: 10.1017/s175173111400189x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of liquid-fed growing pigs provided with straw in various amounts and frequencies

Abstract: Straw possesses many characteristics that make it attractive to pigs and can therefore be effective in preventing negative penmate-directed behaviours. However, straw is difficult to handle in current vacuum slurry systems under most commercial conditions and can therefore only be used in limited amounts. To occupy pigs effectively, straw must remain attractive to pigs throughout the whole day; hence, have a certain degree of novelty. We investigated the penmate-directed behaviour of liquid-fed growing pigs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, after that time they lost interest to the straw, and the conclusion was that the pigs spent interest to the straw just as long as they considered it to be new and unsullied as also concluded by others [29]. Thus a way to stimulate the exploratory behaviour of fatteners could be to more frequently offer small amounts of straw, and/or to let them actively work for feed through automatics [30].…”
Section: Discussionmentioning
confidence: 93%
“…However, after that time they lost interest to the straw, and the conclusion was that the pigs spent interest to the straw just as long as they considered it to be new and unsullied as also concluded by others [29]. Thus a way to stimulate the exploratory behaviour of fatteners could be to more frequently offer small amounts of straw, and/or to let them actively work for feed through automatics [30].…”
Section: Discussionmentioning
confidence: 93%
“…In studies to determine a daily amount of straw after which further increases in quantity no longer reduced penmate manipulation, the resulting values pigs have ranged from 250 g/pig/day (Jensen et al (2015) to slightly below 400 g/pig/day (Pedersen et al, 2014). Pigs given 100 g/day have more overall activity and straw-directed activity than pigs given 25 g/day or 50 g/day, but no difference in manipulation of pen-mates (Oxholm et al 2014). On farms with slatted or partly slatted floors and managing the manure as slurry, few of the above amounts are likely to be adopted, because there is a need to save in labour costs and to prevent obstruction of the manure management system.…”
Section: Introductionmentioning
confidence: 99%
“…It could be that providing a larger amount of straw and thereby ensuring access for a longer period of the day would have reduced the escalation in tail biting more efficiently [27]. Hence, increasing amounts of straw, increases the time pigs interact with the material [28,29]. There are, however, practical problems with larger amounts of straw, as it increases the risk of the material accumulating in the slurry canals or blocking up the slurry pipes [9].…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, practical problems with larger amounts of straw, as it increases the risk of the material accumulating in the slurry canals or blocking up the slurry pipes [9]. To ensure access to straw for a longer period during the day, Oxholm et al [28] demonstrated that more frequent allocation (four times daily vs. once a day) of the same total amount of straw ensured more straw left in the pen the following day. Another approach could be to give the straw in a rack, which would probably also increase accessibility.…”
Section: Discussionmentioning
confidence: 99%